Managing pregnancy in women with Sturge-Weber syndrome: case report and review of the literature. (4th July 2022) - Durai, Vignesh; Sagili, Haritha; Durairaj, Jayalakshmi; Ananthakrishnan, Ramesh; Nair, Pradeep P.; Keepanasseril, Arun; Keepanasseril, Anish
Abstract: Sturge-Weber syndrome (SWS) is a sporadic congenital neuro-cutaneous anomaly with capillary-venous malformation involving the brain, eye, and the ophthalmic division of the trigeminal nerve. In these cases, physiological changes in pregnancy, including hormonal and hemodynamic changes, may predispose to increased seizure frequency and even a life-threatening intracranial haemorrhage. There are only few case reports available about the management of women with pregnancy and SWS. We report two patients with SWS diagnosed in childhood and managed during pregnancy and reviewed the outcomes and complications during pregnancy in women with this disorder.